2023
DOI: 10.3390/agriculture13051004
|View full text |Cite
|
Sign up to set email alerts
|

Study on Monitoring SPAD Values for Multispatial Spatial Vertical Scales of Summer Maize Based on UAV Multispectral Remote Sensing

Abstract: Rapid acquisition of chlorophyll content in maize leaves is of great significance for timely monitoring of maize plant health and guiding field management. In order to accurately detect the relative chlorophyll content of summer maize and study the responsiveness of vegetation indices to SPAD (soil and plant analyzer development) values of summer maize at different spatial vertical scales, this paper established a prediction model for SPAD values of summer maize leaves at different spatial scales based on UAV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Spectral information serves as the foundational data for the optical remote sensing of spectral traits [ 46 , 47 ], and it is determined by various factors such as canopy structure and biochemical composition. Due to the uneven distribution of nutrients along the vertical scale of crops, it is often manifested on the leaves [ 29 ]. Studying the vertical variation in LNC can better elucidate changes in plant physiological processes and adjust the photosynthesis and nutrient absorption of crops, thereby optimizing agricultural management practices more effectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spectral information serves as the foundational data for the optical remote sensing of spectral traits [ 46 , 47 ], and it is determined by various factors such as canopy structure and biochemical composition. Due to the uneven distribution of nutrients along the vertical scale of crops, it is often manifested on the leaves [ 29 ]. Studying the vertical variation in LNC can better elucidate changes in plant physiological processes and adjust the photosynthesis and nutrient absorption of crops, thereby optimizing agricultural management practices more effectively.…”
Section: Discussionmentioning
confidence: 99%
“…This may reduce the quality of observations for these leaves, and the spectral signals at different vertical levels may mix together, especially when the sensor resolution is relatively low. This can make it challenging to differentiate the spectral signals at different vertical levels, and in general, upper leaves usually have more sensitive spectral signals, making them easier to detect and interpret, while the signal mixing at the middle and lower layers may complicate the estimation of LNC [ 29 ]. We observed that the increase in nitrogen application led to a corresponding rise in LNC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in N accumulation in plants treated with HS was consistent with the increase in the SPAD index, but this relationship was significant only under adequate P supply. The SPAD index, calculated using a widely utilized chlorophyll meter in agricultural systems, guides N management via monitoring the leaf N status [ 46 ]. The humate effect on N content without a SPAD index changes under low-P conditions and can be explained via a consideration of the impact on photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…A smaller MSE indicates a higher alignment between predicted and original data. The final optimization yields the best regularization coefficient C and kernel function parameter S. Using these optimized values, the network is trained on the testing dataset [20]. The flowchart of the SSA-KELM algorithm is shown in Figure 3.…”
Section: Model Constructionmentioning
confidence: 99%